Legal Authority of Religious Courts in Annulment of Land Sale Deeds in Indonesia: Jurisdictional Overlaps and Legal Implications - Hayaza, Maria; Idrus, Muammar Alay; Kholidi, M. (Al-Risalah, 2025)
The Religious Court (Pengadilan Agama) and the District Court (Pengadilan Negeri) exercise distinct jurisdictions in civil matters, yet jurisdictional ambiguity often arises in cases involving sale and purchase deeds. In Indonesian civil law, such deeds are crucial legal instruments serving as definitive proof of the transfer of ownership rights. The core legal controversy lies in whether the Religious Court possesses the authority to annul sale and purchase deeds—a matter traditionally under the District Court’s jurisdiction. This study critically examines the authority of the Religious Court in such annulments and the ensuing legal consequences. Employing a normative juridical method with a descriptive-analytical and case approach, the research reveals that while annulment should formally fall under the District Court, the Religious Court may adjudicate when the parties are Muslims. Such annulments carry significant implications, including the restitution of land rights to the aggrieved party and the potential for compensation claims.